The Thermal Tolerance of Springtails in a Tropical Cave, with the Description of a New Coecobrya Species (Collembola: Entomobryidae) from Thailand - Nongnapat Manee; Louis Deharveng; Cyrille A. D’Haese; Areeruk Nilsai; Satoshi Shimano; Sopark Jantarit (Insects)
A new species of Collembola in the genus Coecobrya, C. microphthalma sp. nov., is described from a cave environment in Saraburi province, central Thailand. The new species is the second described species of the boneti-group found in the country. It is most similar to C. chompon Nilsai, Lima & Jantarit, 2022, which is also described from a Thai cave. However, the new species is morphologically different from C. chompon in having orange dot pigmentation on its body and a combination of other morphological characteristics such as the number of sublobal hairs on the maxillary outer lobe and the number of medio-sublateral mac on Th. II, Abd. I, Abd. III and Abd. IV and the anterior face of the ventral tube. The morphological comparison of all known boneti species and a key to the world species of Coecobrya of the boneti-group are given. Coecobrya microphthalma sp. nov. was successfully cultured in the laboratory. The thermal tolerance of the new species was studied and tested with seven different temperature experiments (27 °C as a control, 30, 32, 33, 34, 35 and 36 °C). The results showed that C. microphthalma sp. nov. cannot survive at a temperature higher than 32 °C after exposure to the experimental heat for 7 and 14 consecutive days. At 27, 30 and 32 °C, C. microphthalma sp. nov. remained alive and produced eggs, but the duration of egg production and number of egg-laying days significantly declined when the temperature increased (p < 0.001). An interesting aspect of their reproduction concerns temperature. At 32 °C (5 °C above the control temperature), the F1 generation survived, was active and was able to molt to the adult stage. However, specimens were unable to produce the next generation of offspring. For postembryonic development, C. microphthalma sp. nov. required six molts to reach the adult stage. The development rate (from egg to adult) varied and differed significantly between the tested temperatures (p < 0.001). An increase in temperature from the control temperature significantly accelerated the developmental rate from egg to juvenile instars to adult with a statistical significance (p < 0.01). This study is the first attempt that provide information on the impact of increasing temperature on the population dynamics, reproductive capacity and life history of a subterranean tropical Collembola.